ANALISIS DAMPAK GAME SHOW CLASH OF CHAMPIONS TERHADAP MOTIVASI BELAJAR DI KALANGAN GEN-Z - Lestari, Ratna Ani; Darmawan, Puguh (Fitrah, 2024)
The main problem in this study is the impact that arises after the Clash of Champions game show on YouTube and Ruangguru application. This study aims to examine in depth the impact of the Clash of Champions game show on Gen-Z learning motivation. The analysis of learning motivation in this study uses five aspects including the desire to succeed, having motivation and needs in learning, diligently doing assignments, resilient in facing difficulties, and interesting activities in learning. This type of research is qualitative research with a survey type. The subjects in this study were categorized into two namely students and college students. The research instruments used in this research are questionnaires and interviews. The data analysis technique used is domain data analysis technique. The results showed that both student and student subjects showed the occurrence of learning motivation indicators after the subject watched Clash of Champions. Based on the results of this study, it can be concluded that Clash of Champions has an impact on the enthusiasm and motivation to learn for both students and college students.